Endangered by laws: potential consequences of regulations against thistles on bumblebee conservation. Issue 1 (2nd January 2017) - Vray, Sarah; Lecocq, Thomas; Roberts, Stuart P.M.; Rasmont, Pierre
Summary: Many bumblebee ( Bombus ) species are undergoing a strong decline in Europe due to, amongst other things, a decrease of food resources. While leguminous plants (Fabaceae) are considered to be one of the main pollen sources of bumblebees, thistles (Asteraceae tribe Cardueae) have been suggested to be important for male diet. Yet, several European countries apply strict regulations against thistles since they are considered to be one of the principal weeds in agricultural landscapes. Such regulations could impact bumblebee conservation through disruption of male diet and ecology. Here, we assess the male-depending importance of thistles for bumblebee species based on field observations across countries where a legal regulation against thistles is in effect. We ultimately aim to evaluate the potential consequences of these regulations on bumblebee conservation. Our results confirm that most floral visit observations of males occur on thistles (mainly Cirsium spp. and Carduus spp.) and some species are almost exclusively observed on them. Thistle removal is thus most likely a threat for bumblebees. Therefore, we advocate repealing the thistle removal acts to make way for alternative thistle regulations which reconcile biodiversity conservation and agricultural requirements.